Werbungskosten und Vergleichsberechnung im Wohngeldrecht. - (:unkn) unknown (Werner, 2001)
VG Berlin, Urteil vom 19.10.2000 - VG 21 A 380/99. difu
Keywords: Mietwesen; Wohngeldrecht; Einkommensteuer; Steuer; Werbungskosten; Ausbildungskosten